2023
DOI: 10.3389/fpain.2023.1089748
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the effects of two different kinesiology taping techniques on shoulder pain and function in patients with hypermobile Ehlers-Danlos syndrome

Abstract: BackgroundEhlers-Danlos Syndrome (EDS) is a group of inherited connective tissue disorders which predominantly affects women and has a prevalence as high as 1 in 5,000 individuals. Hypermobile EDS (hEDS) is the most common subtype of EDS and is characterized by multi-joint pain, particularly in large joints such as the shoulder. Physical therapy is often utilized to address the pain, physical impairments, and functional loss in patients with EDS. Kinesiology Tape (KT) is an intervention commonly used by physic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…While our study cannot answer the mechanism through which the K-Tape application improved AROM rotation, we can state that it does not appear to be through improving AJR. In a previous study, using the same taping protocols in patients with hEDS and shoulder pain, it was demonstrated that there was a significant short-term improvement in pain and function after either K-Tape application with no difference between the groups ( 22 ). However, the results of this study favor the experimental tape, indicating that pain reduction may not be the only mechanism for improving the rotational AROM in the experimental K-Tape group.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…While our study cannot answer the mechanism through which the K-Tape application improved AROM rotation, we can state that it does not appear to be through improving AJR. In a previous study, using the same taping protocols in patients with hEDS and shoulder pain, it was demonstrated that there was a significant short-term improvement in pain and function after either K-Tape application with no difference between the groups ( 22 ). However, the results of this study favor the experimental tape, indicating that pain reduction may not be the only mechanism for improving the rotational AROM in the experimental K-Tape group.…”
Section: Discussionmentioning
confidence: 97%
“…All taping utilized the Thrive Far Infrared Kinesiology Tape (Melrose, MA, USA). The taping techniques have been previously described in the literature ( 22 ). However, in brief, the experimental group had the first strip applied from the lateral inferior aspect of the clavicle wrapping around to the medial posterior scapular.…”
Section: Methodsmentioning
confidence: 99%
“…The body of literature on taping techniques has significantly expanded in recent years ( Thelen, Dauber & Stoneman, 2008 ). Studies tend to emphasize immediate gains ( Tudini et al, 2023 ) more prominently than short or long-term effects of tape application. However, it is noteworthy that the majority of research is focused on KT rather than DT.…”
Section: Discussionmentioning
confidence: 99%
“…Simultaneously, the lack of consensus on the biomechanical principles at work, acceptable taping techniques, quantity of tension during application, and application frequency with dosage are still debatable. Moreover, the utility of kinesio-tape (KT) to treat musculoskeletal conditions in athletic population and other musculoskeletal conditions is well documented ( Mostafavifar, Wertz & Borchers, 2012 ; Ferreira, Resende & Roriz, 2017 ; Tudini et al, 2023 ). The introduction of dynamic tapes (DT), characterized by distinct mechanical properties compared to traditional KT, represents a potential advancement in therapeutic applications.…”
Section: Introductionmentioning
confidence: 99%